Mechanical and optical properties of conventional restorative glass-ionomer cements - a systematic review - Rafael MENEZES-SILVA; Renata Nunes CABRAL; Renata Corrêa PASCOTTO; Ana Flávia Sanches BORGES; Carolina Castro MARTINS; Maria Fidela de Lima NAVARRO; Sharanbir K. SIDHU; Soraya Coelho LEAL (University of São Paulo, 2019)
Abstract Objectives To perform a systematic review of test methodologies on conventional restorative glass-ionomer cement (GIC) materials for mechanical and optical properties to compare the results between different GICs. Material and Methods Screening of titles and abstracts, data extraction, and quality assessments of full-texts were conducted in search for in vitro studies on conventional GICs that follow the relevant specifications of ISO standards regarding the following mechanical and optical properties: compressive strength, flexural strength, color, opacity and radiopacity. Sources The Latin American and Caribbean Health Sciences (LILACS), Brazilian Bibliography of Dentistry (BBO) databases from Latin-American and Caribbean System on Health Sciences Information (BIREME) and PubMed/Medline (US National Library of Medicine - National Institutes of Health) databases were searched regardless of language. Altogether, 1146 in vitro studies were selected. Two reviewers independently selected and assessed the articles according to pre-established inclusion/exclusion criteria. Among all the properties investigated, only one study was classified as being of fair quality that tested compressive strength and was included. It was observed that many authors had not strictly followed ISO recommendations and that, for some properties (diametral tensile strength and microhardness), there are no guidelines provided. Conclusions It was not possible to compare the results for the mechanical and optical properties of conventional restorative GICs due to the lack of standardization of studies.